BABAK BARU REJIM KEAMANAN SIBER DI ASIA TENGGARA MENYONGSONG ASEAN CONNECTIVITY 2025 - Indah Novitasari (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2017)
This article discusses the relevance phenomenon of the world community's dependence on the use of cyber space, and the form of cyber security cooperation in Southeast Asia after ASEAN Community 2015. The use of cyber as an implication of information and communication technology progresses not only gives positive impact by shortening the distance, space and time, but in fact negatively impacted by the emergence a new generation of non-traditional threats which called cybercrime. This non-traditional threat appears latent, but has a massive impact on countries in Southeast Asia that have relatively high cyber consumptive levels with low cyber security. This spectrum of non-traditional threats needs to be addressed by efforts to implement a regional cooperation in order to strengthen the civic resilience actively within the global and regional framework. After ASEAN Community 2015, the integration of the region in various fields has also opened the vulnerability of various countries in the region against cybercrime. In facing this threat, ASEAN needs to create a more comprehensive cyber security cooperation framework through cyber security regime in Southeast Asia as an implementation of ASEAN values ​​and norms in realizing the stability of the region. The cyber security regime in Southeast Asia is considered to be a rational choice especially in achieving ASEAN Connectivity in 2025 as an agenda in realizing integration in Southeast Asia Keywords: Cyber, Cyber Security Cooperation in South East Asia, Cyber Security Regime in South East Asia, ASEAN Connectivity 2025. Abstrak Artikel ini merupakan kajian yang membahas keterkaitan fenomena ketergantungan masyarakat dunia terhadap penggunaan ruang Siber, dan bentuk kerjasama Keamanan Siber di kawasan Asia Tenggara pasca berjalannya ASEAN Community tahun 2015. Penggunaan siber sebagai implikasi kemajuan teknologi informasi dan komunikasi, tidak hanya memberikan dampak positif dengan mempersingkat jarak, ruang dan waktu, namun nyatanya memberikan dampak negative dengan munculnya ancaman non-tradisional generasi baru yaitu kejahatan siber. Ancaman non-tradisional ini muncul secara laten, namun berdampak massif bagi negara-negara di Kawasan Asia Tenggara yang memiliki tingkat konsumtif siber relatif tinggi dengan keamanan siber yang rendah. Spektrum ancaman non-tradisional ini kemudian perlu disikapi dengan upaya melaksanakan sebuah kerjasama regional guna memperkuat ketahanan siber yang dilakukan secara aktif dalam kerangka global dan regional. Pasca Komunitas ASEAN 2015, integrasi kawasan dalam berbagai bidang nyatanya juga telah membuka kerentanan berbagai Negara di kawasan terhadap serangan kejahatan siber. Dalam menghadapi ancaman ini, maka ASEAN perlu membuat sebuah kerangka kerjasama keamanan siber yang lebih komprehensif melalui rejim keamanan siber di Asia Tenggara sebagai sebuah implementasi nilai dan norma ASEAN dalam mewujudkan stabilitas kawasan. Rejim Keamanan Siber di Asia Tenggara dinilai menjadi sebuah pilihan rasional terlebih dalam mencapai konektivitas ASEAN tahun 2025 sebagai sebuah agenda dalam mewujudkan integrasi di kawasan Asia Tenggara. Kata Kunci: Siber, Kerjasama Keamanan Siber di Asia Tenggara, Rejim Keamanan Siber di Asia Tenggara, ASEAN Connectivity 2025